TINJAUAN HUKUM ISLAM TERHADAP FASILITATOR PERBUATAN ZINA - Dudi Badruzaman (Tahkim (Jurnal Peradaban dan Hukum Islam), 2020)
ABSTRACTAdultery is now not just an individual act anymore, but has become an "industry" with localization both legal and illegal. In this case many actors are involved in it such as the presence of pimps, sex brokers, providers of places, delivery people, etc. They can be referred to as the facilitator of adultery / obscenity, in addition to the adulterer itself. The purpose of this study is to find out the views of jurisprudence fiqh towards facilitators of assault and sanctions for them. , this study shows that the facilitators of immoral acts are jarimah acts and are included in ta'zir jarimah's part. Judging from the concept of participation, the facilitator of obscene acts includes participating indirectly and depending on the case, can by way of agreement, inciting (ordering), or giving assistance. The sanction for the facilitator of this obscene act is the sanction of ta'zir, the light weight become state rights in accordance with the demands of benefit.Keywords: Islamic Law, facilitator, Zina.